F AND O BAN - AN OPPORTUNITY FOR TRADERS TO GRAB A GOOD PROFIT IN DERIVATIVE MARKET - Mrs. Namrata N. Nadgauda (1), Prof. Dr. Dharmendra (2) (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
In this paper we define future and option F and O ban. How, why and when it comes into action. It also proposes the period of ban, the reason and criteria of banning. It discuss the effect of banning on price of stocks as well as on traders. Finally it concludes about grabbing of handful of profit in banning situation with the help of illustrating examples.